Adrenal Asthenia - Sanjay Kalra,; Atul Dhingra,; Nitin Kapoor, (Journal of the Pakistan Medical Association, 2025)
The terms ‘adrenal asthenia’, ‘adrenal fatigue’ and ‘adrenalburnout’, sometimes used in lay language, are not a part ofthe medical or endocrine lexicon. In this opinion piece, weexplore the relevance of adrenal asthenia and describe howit can be used in different clinical situations, with varyingconnotations. Adrenal asthenia may refer to adrenocorticalinsufficiency, increased parasympathetic or reducedadrenergic tone, or fatigue due to excessive andcontinuous exposure to stress. It may be mediated byhypoglycaemia or dyselectrolytaemia. The term adrenalasthenia has important clinical and public health advantages. Keywords: Adrenal, Addison’s disease, adrenalinsufficiency, person centred care, psychosocial aspects